Farm growth and land concentration - Jana Plogmann; Oliver Mußhoff; Martin Odening; Matthias Ritter (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2020)
Structural change in agriculture is characterized by the interdependency of farms' growth decisions due to the limited availability of the production factor land. This paper adds to the sparse empirical literature on the relation between land market concentration and farm size changes, considering different definitions of the relevant market. Using data from the Integrated Administrative Control System (IACS) from 2005 until 2017 for Brandenburg, Germany, we find that about half of the land transactions occur beyond municipality borders. This emphasizes the importance of carefully defining the relevant market. The descriptive analysis shows that although concentration rates, on average, did not increase over time, spatial differences are present. In the econometric analysis, we apply a two-stage model to analyze how competition for agricultural land impacts the probability and level of expansion. It shows that for farms that remained active between 2005 and 2017, farms that defragment are less likely to expand. Moreover, we find that the expansion behavior between groups of small and large farms differs with increasing inequality. One potential reason for this might be the existence of market power in land markets.
urn:nbn:de:kobv:11-110-18452/22132-5
Keywords: Q13; Q24; 330; farm growth; concentration measures; agricultural land markets; structural change; IACS